Chemometric Analysis for Distribution of Physicochemical Parameters and Heavy Metals of Soil - H., Usman; A. U. , Maigari; A. U. , Maigari; H. K. , Zanna,; I. , Mohammed; M. , Muktari (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This research work was carried out on distribution of physicochemical parameters and heavy metals in soil in the vicinity of Ashaka cement industry, Gombe state. The objective of this study was to determine the concentration of heavy metal in soil sample of the study area and compare the results with standard value by WHO/FAO. 12 soil samples were collected from four (4) sampling sites, following APHA procedures for physicochemical parameters while XRF was used for heavy metals of soil samples. Samples were collected using a composite sampling method during the rainy season of 2023. Soils were sampled using clean plastic bags. Analysis was done for heavy metal concentrations such as Pb, Cr, Cd, As, Co, Ni, Cu and Zn. Chemometric analytical statistical analysis such as Hierarchical Cluster Analysis (HCA), Principal Component Analysis (PCA) and Correlation Analysis (CA) were carried. Unlike the rest of the heavy metal concentrations, the result showed the highest levels for Pb, i.e., 94.2 mg/kg for soil sample in JGS which is ≤ 2Km from the cement factory. On the other hand, the mean concentration of heavy metals in the soil sample showed a strong positive correlation between Cd to Cd, Co, and Pb at +1, +0.572 and +0.68 respectively which shows they are all from the same source of pollutant. The study also revealed that most of the heavy metal concentration recorded increased in content during the month of August/September over the month of July/October, due to the surface run off from storm water. The research therefore recommended that although it is indispensable to monitor constantly the quality of soil to avoid the penetration of heavy metals, the government should provide rules and regulations that hinder the dumping of industrial effluent on farmlands to avoid further enrichment of the soil with heavy metals.